Evaluation of Hepatoprotective Activity of Caralluma europaea Stem Extract against CCl4-Induced Hepatic Damage in Wistar Rats - Hayat Ouassou; Mohamed Bouhrim; Nour Elhouda Daoudi; Hassane Mekhfi; Abderrahim Ziyyat; Abdelkhaleq Legssyer; Mohamed Aziz; Mohamed Bnouham (Hindawi Limited, 2021)
The present study aims to evaluate the hepatoprotective activity of stem aqueous extract of Caralluma europaea (AECe) on carbon tetrachloride- (CCl4-) induced hepatic damage in Wistar rats. The animals were daily treated with the aqueous extract of C. europaea at a dose of 250 mg/kg body weight for 14 days. CCl4 was injected (1 ml/kg, i.p.) two times, on the 7th and 14th days. At the end of the experimental period, all rats were anesthetized to collect blood for the assessment of biochemical parameters and then sacrificed to collect the liver for weighing. Hepatotoxicity was evaluated by measuring the serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), bilirubin (total and direct), malondialdehyde (MDA), total protein (TP), triglycerides (TG), total cholesterol, very low-density lipoprotein (VLDL-c ), low-density lipoprotein (LDL-c), high-density lipoprotein (HDL-c), urea, creatinine, and uric acid. Based on the results obtained in this study, the administration of C. europaea before exposure to the administration of CCl4 conferred favorable hepatoprotective effect in rats. The treatment with AECe (250 mg/kg) exhibits a significant hepatoprotective effect by ameliorating CCl4-induced alterations of these biochemical parameters. Hence, C. europaea could be a potential medicinal herb that can be used in the future to prevent liver intoxication.